Case Report: Early Resection of Pheochromocytoma in a Patient With Cardiogenic Shock Due to Pheochromocytoma-Induced Cardiomyopathy With Extracorporeal Life Support - Lyu, Ting; Niu, Jianhua; Liu, Zhihai; Li, Tong (Frontiers in Cardiovascular Medicine, 2022)
Background Pheochromocytoma-induced cardiomyopathy is a rare but potentially life-threatening complication of pheochromocytoma. It mimics the patterns of stress-induced cardiomyopathy. In severe cases, patients can develop refractory cardiogenic shock, which might require mechanical circulatory support. Case Presentation We presented a case of 54-year-old female who developed refractory cardiogenic shock, following an elective orthopaedic surgery complicated by cardiac arrest, requiring veno-arterial extracorporeal membrane oxygenation (VA-ECMO) support. After urgent coronary catheterisation revealed normal coronary arteries, further evaluation of the aetiology of cardiogenic shock revealed pheochromocytoma. With a diagnosis of pheochromocytoma-induced cardiomyopathy, the patient had accelerated preoperative alpha adrenergic blockade preparation for a total of 6 days and subsequently had the tumour removed under VA-ECMO support. Postoperatively, the patient recovered well and was off ECMO support and extubated a few days later. The optimal management of pheochromocytoma-induced cardiomyopathy, especially for severe cases, is still unclear. Indeed, some cases will require mechanical circulatory support to allow left ventricular function recovery. But our case also showed that it was possible to introduce alpha blockade safely whilst the patient is on VA-ECMO and has the pheochromocytoma removed with VA-ECMO support after accelerated preoperative preparation.